Taking the Wheel – de novo DNA Methylation as a Driving Force of Plant Embryonic Development - Markulin, Lucija; Škiljaica, Andreja; Tokić, Mirta; Jagić, Mateja; Vuk, Tamara; Bauer, Nataša; Leljak Levanić, Dunja (Frontiers in Plant Science, 2021)
During plant embryogenesis, regardless of whether it begins with a fertilized egg cell (zygotic embryogenesis) or an induced somatic cell (somatic embryogenesis), significant epigenetic reprogramming occurs with the purpose of parental or vegetative transcript silencing and establishment of a next-generation epigenetic patterning. To ensure genome stability of a developing embryo, large-scale transposon silencing occurs by an RNA-directed DNA methylation (RdDM) pathway, which introduces methylation patterns de novo and as such potentially serves as a global mechanism of transcription control during developmental transitions. RdDM is controlled by a two-armed mechanism based around the activity of two RNA polymerases. While PolIV produces siRNAs accompanied by protein complexes comprising the methylation machinery, PolV produces lncRNA which guides the methylation machinery toward specific genomic locations. Recently, RdDM has been proposed as a dominant methylation mechanism during gamete formation and early embryo development in Arabidopsis thaliana, overshadowing all other methylation mechanisms. Here, we bring an overview of current knowledge about different roles of DNA methylation with emphasis on RdDM during plant zygotic and somatic embryogenesis. Based on published chromatin immunoprecipitation data on PolV binding sites within the A. thaliana genome, we uncover groups of auxin metabolism, reproductive development and embryogenesis-related genes, and discuss possible roles of RdDM at the onset of early embryonic development via targeted methylation at sites involved in different embryogenesis-related developmental mechanisms.